PENINGKATAN KOMPETENSI GURU DALAM PELAKSANAKAN PEMBELAJARAN KURIKULUM 2013 DENGAN METODE TEMAN SEJAWAT ( PEER COUCHING ) DI SDN 010 PAGARAN TAPAH DARUSSALAM - -, Hj. Sri Rahayu (Universitas Pasir Pengaraian, 2015)
This study aims to improve the implementation of learning competencies incurriculum in 2013 with the method peers (peer coaching) in SD Negeri 010 Pagaran Tapah Darussalam. The subjects of this study were teachers SDN 010 Pagaran Tapah Darussalam as many as 10 peoples. School action research conducted in two cycles. Collecting data in this study using the methods of supervision. Data from research on teacher competence in the implementation of the learning curriculum in 2013 with the method peers (peer coaching) at SDN 010 Pagaran Tapah Darussalam. The results showed that an increase in the competence of teachers in the implementation of the learning curriculum at SDN 010 2013 Pagaran Tapah Darussalam with methods peers (peer coaching) has been proven to get results before Peer held couching only 4 teachers who can implement curriculum learning in 2013 correctly. In the second cycle showed an increase in the number of teachers who can implement curriculum in 2013 as many as 10 peoples.